Value-based healthcare for social insurance medicine: key enablers for adoption in practice - Sylvia J van der Burg-Vermeulen; Philip J van der Wees; Jan L Hoving; Nina Zipfel; Marijke Melles; Marije E Hagendijk (BMJ Open Quality)
Background Driven by rising retirement age and increasing prevalence of chronic diseases impacting work participation, there is an increasing need for quality and efficiency improvement in social insurance medicine (SIM). SIM provides guidance to individuals facing long-term work disability, assess their functional abilities and eligibility for long-term disability benefits. Value-based healthcare (VBHC) targets quality and efficiency improvements in healthcare by placing a priority on improving patient value. So far, VBHC has been introduced with fundamental principles and essential components for its adoption in curative care. Hence, there is room for debate on what are key enablers for the adoption of value-based SIM.Purpose The study aims to explore key enablers for the adoption of VBHC in the practice of SIM.Methods In this exploratory qualitative study, participants consisted of 15 professionals with expertise either in SIM (n=10) or with expertise in the adoption of VBHC in the curative care sector (n=5). Each participant took part in both a semistructured individual interview and a focus group interview. Thematic coding was employed to analyse the data.Results Seven key enablers were identified: (1) investigate the meaning and implementation constraints of value in SIM, (2) integrate SIM into work-focused care networks, (3) explore the need and feasibility for specialisation based on functional problems, (4) identify the most important work outcomes for the patient, (5) identify proxy indicators for cost drivers, (6) identify value-driven financial incentives and (7) develop an information technology system to exchange data.Conclusions This paper provides understanding of what is needed to adopt value-based SIM. Future research should delve deeper into these seven key enablers to facilitate the adoption of VBHC, and thereby promote value creation in the practice of SIM.